Prevalence of Hypertension and Its Associated Risk Factors among Adults in Pakistan. - Rasool, Ghazala; Khan, Sayed; Abro, Aftab Hussain; Shafi, Hasan; Ahmed, Naseer; Sabah, Noor us (Journal of Neonatal Surgery, 2025)
Introduction: Hypertension is a non-communicable disease and a significant risk factor for cardiovascular morbidity and mortality worldwide. The incidence of hypertension in Pakistan is increasing, although community-level statistics about its factors are scarce. This study sought to evaluate the prevalence of hypertension and its related risk factors among individuals in several Pakistani communities. Materials and Methods: A community-based cross-sectional study was performed from January to June 2024. A total of 88 participants aged 18 years and older were recruited by multistage sampling. Information regarding socio-demographic variables, lifestyle practices, medical history, and family history was gathered utilizing a pre-tested structured questionnaire. Blood pressure and anthropometric data were acquired using defined protocols. Hypertension is characterized by a systolic blood pressure of ≥140 mmHg, a diastolic blood pressure of ≥90 mmHg, or the current administration of antihypertensive medication. Data were evaluated utilizing SPSS v25, and logistic regression was employed to ascertain independent risk factors. Results: The total prevalence of hypertension was 34.1% (30 out of 88). It was more prevalent among participants aged 45 years and older, those with a BMI of 25 kg/m² or above, and persons with low levels of physical activity. Smoking and a positive family history were substantially correlated with hypertension in bivariate analysis, although gender exhibited no significant correlation. In multivariable analysis, age ≥45 years (AOR = 3.12), BMI ≥25 kg/m² (AOR = 2.85), and low physical activity (AOR = 2.67) were identified as independent predictors of hypertension, with the total regression model demonstrating statistical significance and accounting for 34% of the variance in hypertension status. Conclusion: Hypertension is prevalent among Pakistani adults, with modifiable risk factors including obesity and inactivity. Community-based screening and lifestyle interventions are essential to reduce its burden, and larger studies are needed to inform targeted prevention strategies..